Secretome Analysis from the Ectomycorrhizal Ascomycete Cenococcum geophilum - de Freitas Pereira, Maíra; Veneault-Fourrey, Claire; Vion, Patrice; Guinet, Fréderic; Morin, Emmanuelle; Barry, Kerrie W.; Lipzen, Anna; Singan, Vasanth; Pfister, Stephanie; Na, Hyunsoo; Kennedy, Megan; Egli, Simon; et al. (Frontiers in Microbiology, 2018)
Cenococcum geophilum is an ectomycorrhizal fungus with global distribution in numerous habitats and associates with a large range of host species including gymnosperm and angiosperm trees. Moreover, C. geophilum is the unique ectomycorrhizal species within the clade Dothideomycetes, the largest class of Ascomycetes containing predominantly saprotrophic and many devastating phytopathogenic fungi. Recent studies highlight that mycorrhizal fungi, as pathogenic ones, use effectors in form of Small Secreted Proteins (SSPs) as molecular keys to promote symbiosis. In order to better understand the biotic interaction of C. geophilum with its host plants, the goal of this work was to characterize mycorrhiza-induced small-secreted proteins (MiSSPs) that potentially play a role in the ectomycorrhiza formation and functioning of this ecologically very important species. We combined different approaches such as gene expression profiling, genome localization and conservation of MiSSP genes in different C. geophilum strains and closely related species as well as protein subcellular localization studies of potential targets of MiSSPs in interacting plants using in tobacco leaf cells. Gene expression analyses of C. geophilum interacting with Pinus sylvestris (pine) and Populus tremula × Populus alba (poplar) showed that similar sets of genes coding for secreted proteins were up-regulated and only few were specific to each host. Whereas pine induced more carbohydrate active enzymes (CAZymes), the interaction with poplar induced the expression of specific SSPs. We identified a set of 22 MiSSPs, which are located in both, gene-rich, repeat-poor or gene-sparse, repeat-rich regions of the C. geophilum genome, a genome showing a bipartite architecture as seen for some pathogens but not yet for an ectomycorrhizal fungus. Genome re-sequencing data of 15 C. geophilum strains and two close relatives Glonium stellatum and Lepidopterella palustris were used to study sequence conservation of MiSSP-encoding genes. The 22 MiSSPs showed a high presence-absence polymorphism among the studied C. geophilum strains suggesting an evolution through gene gain/gene loss. Finally, we showed that six CgMiSSPs target four distinct sub-cellular compartments such as endoplasmic reticulum, plasma membrane, cytosol and tonoplast. Overall, this work presents a comprehensive analysis of secreted proteins and MiSSPs in different genetic level of C. geophilum opening a valuable resource to future functional analysis.